Living Hadis Tradisi Baburu Kandiak Pada Masyarakat Minangkabau - Bunga Fitria Febriyanti (IAIN Syekh Nurjati Cirebon, 2021)
This research is about the tradition of the baburu kandiak in Minangkabau, Sungai Pua District, Agam Regency, West Sumatra. This study aims to determine the traditions used as a basis for hunting and to determine the role of hadith and the implications of hadith in the hunting process in the Minangkabau tradition. This research is a type of qualitative research. Data was collected using participatory observation and interviews. The results showed that hunting has become a habit of the Minangkabau people, especially the Sungai Pua District, Agam Regency, West Sumatra. Dogs that are kept well to guard homes, livestock, rice fields, fields, and are used as hog hunting animals that damage land and human settlements. Pig hunting activities are carried out by both young and middle-aged men, from rural and urban areas. Hunted objects are animals that are disturbing and detrimental to the community in the agricultural and plantation sectors such as wild boars. The conclusion of the study shows that the Minangkabau people do not base their activities on the tradition of Babur Kandiak on the hadith of the Prophet Muhammad SAW. The internalization of the value of hadith on traditional hunting in the Minangkabau community is that people who are Muslim do not eat hunted pigs. Game animals are eaten by hunting dogs. The hadith of the Prophet Muhammad SAW explains that hunting using dogs is permissible, but there are conditions that must be met. Some scholars are of the opinion that the prey must first be cleaned with air up to seven times. Other scholars are of the opinion that hunting is unnecessary and halal to eat. Baburu Kandiak in Minangkabau is not used for food, but to protect agricultural areas from wild boar pests. The manifest functions of Baburu Kandiak are as follows: First, mutual cooperation to eradicate pig pests; Second, exercise and maintain health; Third, recreation and tourism.